(untitled) (Journal of Nepal Geological Society, 2010)
Different assemblies of granular materials are generated with varying solid fractions and are sheared in the 2D experimental shear flow apparatus with the objective of developing efficient contact detection methodology. The flow is recorded by high speed video camera, and the spatial positions of particle centers are obtained through image processing techniques. The experimental setup was managed to inspect the collision, collision time and collision partners while the experiment is on. Important observations of pre- and post- collision phenomena were made in order to find the precise criteria for distinguishing contacts. Based on these observations together with simple rules of physics, new contact detection algorithm is proposed. The results obtained from proposed method are compared with the visual observations in the digital video of the physical experiment with the help of motion analytical and particle tracking PTV software. It is revealed that the proposed method could detect the contacts with more than 90 percent accuracy in an average and is considerably accurate than the existing methods of contact detection in the physical experiments.